AN IMAGINARY WORSENING STATE IN EPILEPSY - M. B. Mironov; I. V. Okuneva; K. Yu. Mukhin (Русский журнал детской неврологии)
Imaginary worsening in epilepsy is a state in which the patient and his family tell a physician about the increased frequency of the existing seizures or the occurrence of new types of paroxysms after the accurate diagnosis of epilepsy and the prescription of antiepileptic drugs (according to the form of the disease and types of seizures). At the same time, careful medical questioning and additional examination involving prolonged video-electroencephalographic monitoring prove that proximal states that are a patient’s complaints have no epileptic cause and hence a worsening of the disease is absent.